Consumer Dispute Settlement: A Comparative Study on Indonesian and Malaysian Law - Sari, Norma (Faculty of Law, Padjadjaran University, 2018)
Consumer dispute settlement becomes an important instrument for protecting consumers. This study aims toanalyze (i) the urgency of consumer dispute settlement body and small claim mechanism; (ii) the comparisonof consumer dispute settlement law in Indonesia and Malaysia; (iii) a lesson from Malaysia concerning smallclaim court. This research was conducted as a library research. The results show that uurgency of consumerdispute settlement body and small claim mechanism are to guarantee ultimate consumer interest. Comparingof consumer dispute settlement law in Indonesia and Malaysia, each institution and mechanism havingadvantages and disadvantages to consider for betterment in the future. Consumer Dispute Agency is a middleway or a combination off SCC system and specific dispute resolution body. But, Indonesia needs to reiteratethe existing Consumer Protection Act regarding the duty and authority of Consumer Dispute SettlementAgency. There is authority overlap with other agencies needed to be addressed.